Olympic distance duathlon and cardiac performance in highly-trained triathletes - Donaldson, J. A.; Wiles, J. D.; Papadakis, M.; Sharma, S.; Sharma, R.; O'Driscoll, J. M. (Physiological Reports, 2024)
The effects of triathlon exercise on cardiac function are well documented. While Olympic triathlon (swim-bike-run) remains the standard format, increasing concerns about water quality in natural waterways present ongoing challenges for open-water swimming events, highlighting the potential need to consider alternative formats such as duathlon (run-bike-run) in some circumstances. An additional run may increase the overall metabolic and cardiovascular demand compared with the swim in triathlon, leading to reduced future performance. Conversely, the majority of EICF research reports reversal of post-exercise perturbations within 24-7 days of recovery but duathlon has not yet been studied in this context. Therefore, this study aimed to investigate the cardiac, autonomic, haemodynamic and biomarker responses during and following two Olympic distance (OD) duathlon separated by 7 days of recovery. Highly-trained (VO2max >60 mL·kg-1·min-1) male participants (n = 10) completed two lab-based OD duathlons, either continuous (BD) or with functional measurements after each leg (UD), separated by 7 days of rest. Conventional echocardiography recorded standard and tissue Doppler measures of left ventricular (LV) structure and function. Speckle tracking echocardiography was used to measure global longitudinal strain (GLS). Time and frequency domain analysis of HRV, as well as plasma high sensitivity cardiac troponin T (hs-cTnT) were measured pre and post exercise. In the broken duathlon trial (BD) cardiac measurements and blood samples were also taken between each leg. In the unbroken duathlon (UD) participants performed each leg sequentially. Duathlon exercise resulted in similar cardiac functional and biomarker alterations as previously reported in triathlon and standalone running and cycling exercise. Cardiac troponins were still elevated following 24 h-1 of recovery. However, functional changes were resolved within 24 h-1 of passive recovery and did not impair subsequent duathlon performance, or pre-exercise measurements 7 days after the first trial. Whether or not elite or recreational athletes experience the same magnitude and reversibility of these changes remains to be elucidated further.